2019
DOI: 10.1101/2019.12.21.884759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-cell atlas of the human healthy airways

Abstract: 248 words) Rationale: The respiratory tract constitutes an elaborated line of defense based on a unique cellular ecosystem. Single-cell profiling methods enable the investigation of cell population distributions and transcriptional changes along the airways. Methods:We have explored cellular heterogeneity of the human airway epithelium in 10 healthy living volunteers by single-cell RNA profiling. 77,969 cells were collected by bronchoscopy at 35 distinct locations, from the nose to the 12 th division of the ai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
184
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(199 citation statements)
references
References 43 publications
(34 reference statements)
13
184
2
Order By: Relevance
“…It was recently reported that nasal RE has higher expression of CoV-2 entry genes than RE of the trachea or lungs 45 , and we therefore asked where OE fell within this previously established spectrum of expression. We took advantage of recently published data from Deprez and colleagues 46 in which biopsies of healthy human donors that spanned the nasal RE to the distal lung were subject to scSeq. To compare the gene expression levels in this respiratory dataset to those in the nasal mucosa-specific samples in the Durante et al dataset 48 , we sought a mapping between cells in these two datasets to establish a common scale of gene expression.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was recently reported that nasal RE has higher expression of CoV-2 entry genes than RE of the trachea or lungs 45 , and we therefore asked where OE fell within this previously established spectrum of expression. We took advantage of recently published data from Deprez and colleagues 46 in which biopsies of healthy human donors that spanned the nasal RE to the distal lung were subject to scSeq. To compare the gene expression levels in this respiratory dataset to those in the nasal mucosa-specific samples in the Durante et al dataset 48 , we sought a mapping between cells in these two datasets to establish a common scale of gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Data from Deprez et al 46 were downloaded from the European Genomephenome Archive at accession EGAS00001004082. A subset of these data was combined with a subset of the Durante data for mapping between cell types.…”
Section: Mapping Scseq Datasets To Each Othermentioning
confidence: 99%
See 3 more Smart Citations